Pharmacogenomic-guided opioid prescribing in hospice: reducing toxicity while maximizing symptom relief - Ben Thompson; Carrie Hyde; Binoy Singh (Frontiers in Medicine, 2026)
Hospice care centers on interdisciplinary-driven, patient-focused, comprehensive and individualized care at the end of life. Effective pain management has been a cornerstone of hospice care, with up to 80% of patients experiencing moderate to severe pain at the end of life. Although central to hospice care, opioid prescribing faces major challenges: wide variability in response, frequent adverse effects (sedation, constipation, respiratory depression, cognitive impairment), and high rates of uncontrolled pain (20%–40% of patients inadequately relieved despite optimization). Traditional trial-and-error approaches are challenging in hospice due to short prognoses, complex comorbidities, and prevalent polypharmacy. Supportive evidence for the inclusion of Pharmacogenomics (PGx) testing into opioid prescribing is growing. Incorporating PGx testing into opioid prescribing practices at the end of life will face several hurdles including shifting protocols, cost of testing, and ethical concerns. With policy reforms, prescriber training, and rigorous research, PGx may become a useful tool in delivering truly personalized end-of-life care.